2023
DOI: 10.3390/ph16081058
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Nisin as a Means for Improvement of Its Pharmacological Properties: A Review

Abstract: Lantibiotics are believed to have a conceivable potential to be used as therapeutics, especially against clinically resistant bacterial strains. However, their low solubility and poor stability under physiological conditions limit their availability for clinical studies and further pharmaceutical commercialization. Nisin is a readily available and cheap lanthipeptide and thus serves as a good model in the search for the tools to engineer lantibiotics with improved pharmacological properties. This review aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…Most importantly, FM and TEM results showed that nisin promptly reacts with Xf within the first 15 min of contact, leading to an immediate and complete lysis of the cellular membrane and with high potency. This observed effect aligns with the well-documented attributes of nisin, characterized by cationic and hydrophobic peptides ( Musiejuk and Kafarski, 2023 ). The rapid and robust impact of nisin on Xf cells over a brief timeframe is most probably due to the high binding affinity of nisin to lipid II, disrupting the lipid bilayer.…”
Section: Discussionsupporting
confidence: 87%
“…Most importantly, FM and TEM results showed that nisin promptly reacts with Xf within the first 15 min of contact, leading to an immediate and complete lysis of the cellular membrane and with high potency. This observed effect aligns with the well-documented attributes of nisin, characterized by cationic and hydrophobic peptides ( Musiejuk and Kafarski, 2023 ). The rapid and robust impact of nisin on Xf cells over a brief timeframe is most probably due to the high binding affinity of nisin to lipid II, disrupting the lipid bilayer.…”
Section: Discussionsupporting
confidence: 87%
“…This broad substrate specificity of the nisin dehydrating and transport machinery suggests that lantibiotic enzymes could be utilized for the synthesis of a wide range of novel dehydroresidue-containing peptides or novel lantibiotic structures. Building upon these advantages, nisin has been bioengineered to enhance its antimicrobial activity, heat stability, solubility, diffusion, and protease sensitivity. , In this study, we further expand the utility of nisin-controlled expression systems and NisBTC modification machinery, which uses a method for inducing modification enzymes in advance to enhance the peptide modification efficiency (Figure ). The development of an efficient heterologous modification system offers significant advantages, facilitating the characterization and further modification of novel lantibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Lantibiotics are gene-encoded, a feature that makes them amenable to bioengineering. Mutagenesis of lantibiotics has been widely performed to improve their antimicrobial and physicochemical properties . Nisin Z is cationic due to the presence of four positively charged residues (K12, K22, K34, and H31) and the absence of negatively charged equivalents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the pyrophosphate portion of lipid II is removed, the affinity of nisin for lipid II decreases dramatically [9]. After the N-terminal sequence binds to the cell wall and forms a cage-like structure, the C-terminal sequence of nisin flips over into the bacterial cell membrane [10]. In this process, the hinge-like region that connects the two structural domains also plays an important role.…”
Section: The Structure Of Nisinmentioning
confidence: 99%